Postoperative Delirium and Postoperative Cognitive Dysfunction: Overlap and Divergence. (September 2019) - Daiello, Lori A.; Racine, Annie M.; Yun Gou, Ray; Marcantonio, Edward R.; Xie, Zhongcong; Kunze, Lisa J.; Vlassakov, Kamen V.; Inouye, Sharon K.; Jones, Richard N.; Alsop, David; Travison, Thomas; Arnold, Steven; et al.
Editor's Perspective: What We Already Know about This Topic: Postoperative delirium and postoperative cognitive dysfunction both occur in a substantial number of older surgical patients Postoperative delirium and postoperative cognitive dysfunction share risk factors and may co-occur, although their relationship is unclear What This Article Tells Us That Is New: Postoperative delirium increased the risk of postoperative cognitive dysfunction at 1 month postoperatively but there was no association between postoperative delirium and cognitive dysfunction at 2 and 6 months after major noncardiac surgery Postoperative delirium and longer-term postoperative cognitive dysfunction may be different disorders Background: Postoperative delirium and postoperative cognitive dysfunction share risk factors and may co-occur, but their relationship is not well established. The primary goals of this study were to describe the prevalence of postoperative cognitive dysfunction and to investigate its association with in-hospital delirium. The authors hypothesized that delirium would be a significant risk factor for postoperative cognitive dysfunction during follow-up. Methods: This study used data from an observational study of cognitive outcomes after major noncardiac surgery, the Successful Aging after Elective Surgery study. Postoperative delirium was evaluated each hospital day with confusion assessment method–based interviews supplemented by chart reviews. Postoperative cognitive dysfunction was determined using methods adapted from the International Study of Postoperative Cognitive Dysfunction. Associations between delirium and postoperative cognitive dysfunction were examined at 1, 2, and 6 months. Results: One hundred thirty-four of 560 participants (24%) developed delirium during hospitalization. Slightly fewer than half (47%, 256 of 548) met the International Study of Postoperative Cognitive Dysfunction-defined threshold for postoperative cognitive dysfunction at 1 month, but this proportion decreased at 2 months (23%, 123 of 536) and 6 months (16%, 85 of 528). At each follow-up, the level of agreement between delirium and postoperative cognitive dysfunction was poor (kappa less than .08) and correlations were small ( r less than .16). The relative risk of postoperative cognitive dysfunction was significantly elevated for patients with a history of postoperative delirium at 1 month (relative risk = 1.34; 95% CI, 1.07–1.67), but not 2 months (relative risk = 1.08; 95% CI, 0.72–1.64), or 6 months (relative risk = 1.21; 95% CI, 0.71–2.09). Conclusions: Delirium significantly increased the risk of postoperative cognitive dysfunction in the first postoperative month; this relationship did not hold in longer-term follow-up. At each evaluation, postoperative cognitive dysfunction was more common among patients without delirium. Postoperative delirium and postoperative cognitive dysfunction may be distinct manifestations of perioperative neurocognitive deficits. Abstract : Postoperative delirium increased the risk of postoperative cognitive dysfunction at 1 month postoperatively but there was no association between postoperative delirium and cognitive dysfunction at 2 and 6 months after major noncardiac surgery. Postoperative delirium and longer-term postoperative cognitive dysfunction may be different disorders.